Allelopathic effects of Lafoensia glyptocarpa Koehne on Sesamum indicum L. and on the growth of Triticum aestivum L. coleoptiles. - Moraes, Luiza Paiva Silva de (2014)
This study evaluated the allelopathic potential of leaf and root extracts of Lafoensia glyptocarpa Koehne on seed germination and the growth of seedlings and sesame (Sesamum indicum L.) metaxylem cells. We found that the leaf and root extracts of L. glyptocarpa changed in sesame seed germination and seedling growth, as well as changes in the primary root and decreased size and number of metaxylem cells. Leaf extracts were also obtained with hexane, dichloromethane, ethyl acetate, acetone, and methanol, and tested when developing wheat coleoptiles, and the last four showed activity. By subfractioning the ethyl acetate extract,which was the most promising, inhibitory activity ceased for subfractions, and the presence of synergism was subsequently found between them.